BRITE observations of ν Centauri and γ Lupi, the first non-eclipsing members of the new class of nascent binaries. Issue 4 (24th March 2021) - Jerzykiewicz, M; Pigulski, A; Michalska, G; Moździerski, D; Ratajczak, M; Handler, G; Moffat, A F J; Pablo, H; Popowicz, A; Wade, G A; Zwintz, K
ABSTRACT: Results of an analysis of the BRITE-Constellation and Solar Mass Ejection Imager photometry and radial-velocity observations, archival and new, of two single-lined spectroscopic binary (SB) systems ν Centauri and γ Lupi are reported. In the case of γ Lup AB, a visual binary, an examination of the light-time effect shows that component A is the SB. Both ν Cen and γ Lup exhibit light variations with the orbital period. The variations are caused by the reflection effect, i.e. heating of the secondary's hemisphere by the early-B main sequence (MS) primary component's light. The modelling of the light curves augmented with the fundamental parameters of the primary components obtained from the literature photometric data and Hipparcos parallaxes, shows that the secondary components are pre-MS stars, in the process of contracting on to the MS. ν Cen and γ Lup A are thus found to be non-eclipsing counterparts of the B2 IV eclipsing binary (and a β Cephei variable) 16 (EN) Lac, the B5 IV eclipsing binary (and an SPB variable) μ Eri, and the recently discovered Large Magellanic Cloud nascent eclipsing binaries.